Network analysis of caffeine use disorder, withdrawal symptoms, and psychiatric symptoms - Mohammadreza Davoudi; Fatemeh Abdoli; Fereshte Momeni; Mojtaba Habibi Asgarabad (BMC Psychiatry)
Abstract Objective Caffeine Use Disorder (CUD) is not currently recognized as a formal diagnosis in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). However, recent studies within the DSM-5 context have explored this issue. Also, this disorder is closely associated with caffeine withdrawal symptoms, which are formally recognized as a diagnosis in the DSM-5. Additionally, there is limited evidence regarding the connection between caffeine-related issues and psychiatric symptoms. The main aim of the present study was to determine the network structure of CUD and caffeine withdrawal symptoms among the general population. Also, the bridge symptoms among CUD, psychiatric symptoms, and caffeine withdrawal have been estimated. Method Participants were 1228 adults (50.3% females, Mean age (x̄±sd) 35.49 ± 11.70 years) who completed Caffeine Use Disorder Questionnaire (CUDQ), Caffeine Withdrawal Symptoms Questionnaire (CWSQ), and Symptom Checklist-25 (SCL-25). All estimations were conducted according to the Gaussian Graphical Model. Results “Excessive consumption” and “role obligations” were central symptoms in the CUD network. Difficulty in concentration was the most central node in the caffeine withdrawal network. Also, the obsessive-compulsive symptom emerged as a central and highly influential node in the relationship between caffeine-related nodes and psychiatric symptoms. Conclusions Mental health providers should target these specific symptoms in clinical interventions to mitigate caffeine-related problems among individuals in the general population effectively.